Outcomes of combined keratoplasty and pars plana vitrectomy for endophthalmitis with compromised corneal clarity. (23rd August 2018) - Dave, Abhishek; Acharaya, Manisha; Agarwal, Manisha; Dave, Prachi A; Singh, Manisha; Mathur, Umang
Abstract: Importance: Studies evaluating combined penetrating keratoplasty and pars plana vitrectomy for infectious aetiologies are limited. Background: To evaluate the outcomes of combined penetrating keratoplasty and pars plana vitrectomy in patients with endophthalmitis and poor corneal clarity. Design: Retrospective interventional case series conducted at a tertiary care eye hospital in North India. Participants: Review of records of 43 eyes of 43 patients. Mean age of patients was 53.39 ± 12.94 years (26 males). Patients with age > 14 years with minimum follow‐up of 6 months were included. Methods: Combined penetrating keratoplasty and pars plana vitrectomy was performed in all eyes. Main Outcome Measures: We analysed the preoperative, intraoperative and microbiological characteristics of patients undergoing combined surgeries. Anatomic and functional success and failure were pre‐defined. Results: Aetiology for corneal opacification was corneal ulcer in 30(69.7%) eyes, corneal graft infection in eight(18.6%) eyes, bullous keratopathy in four (9.3%) eyes and corneal scar in one eye. Postoperative visual acuity improved in 20(46.5%) eyes, did not change in 14 (32.5%) eyes and deteriorated in nine eyes (20.9%). Anatomical failure (uncontrolled infection leading to phthisis bulbi or evisceration) was seen in 15 (34.8%) eyes. Microbiological analysis revealed bacterial growth in 26, fungal in 14 and no growth in three eyes. Fungal infection had a poorer outcome ( P = 0.03). Six out of 11 monoocular patients regained ambulatory vision. Conclusions and Relevance: Combined penetrating keratoplasty and pars plana vitrectomy is a complex but globe salvaging procedure for poor prognosis eyes which otherwise may need evisceration. Fungal infection carries a poorer prognosis.